Selection and molecular characterization of Bacillus thuringiensis isolates for controlling Spodoptera spp. - Constanski, Kelly Christiane; Zorzetti, Janaina; Vilas Boas, Gislayne Trindade; Ricietto, Ana Paula Scaramal; Fazion, Fernanda Aparecida Pires; Vilas Boas, Laurival; Monnerat, Rose Gomes; Neves, Pedro Manuel Oliveira Janeiro (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to select and molecularly characterize Bacillus thuringiensis isolates toxic to Spodoptera eridania and S. frugiperda. Thirty four isolates were subjected to the bioassay, of which three were selected and used to estimate the LC50. The selected isolates did not differ from the HD‑1 standard line. In the molecular characterization, the presence of the cry1 and cry2 genes was identified in the BR37 and BR94 isolates, and of the cry4A, cry4B, cry10, cry11, and cyt1 genes in the BR58 isolate, which confirmed the obtained protein profile of 130, 70, and 65 kDa. Bipyramidal and spherical crystals were identified. The BR58 isolate, although not containing the genes related to toxicity to Lepidoptera, causes mortality in both species.
Keywords: Spodoptera eridania; Spodoptera frugiperda; biological control; cry genes; Cry proteins